"Faking it" and affectionate communication: Exploring the authenticity of orgasm and relational quality indicators. (1st December 2019) - Denes, Amanda; Horan, Sean M.; Bennett, Margaret
Abstract: Pretending to orgasm is a unique behavior that may be indicative of underlying relational issues, but alternatively, it may be considered a form of affectionate communication if it is rooted in feelings of fondness and caring for one's partner. To further explore these possibilities, two studies were conducted to investigate differences in relational quality indicators for individuals who experienced orgasm, did not experience orgasm, or pretended to orgasm and whether trait affectionate communication moderated these associations. The results of Study 1 revealed that individuals who experienced orgasm reported the highest levels of trust, closeness, and commitment, generally followed by those who pretended to orgasm, with the lowest levels for those who did not experience orgasm. Study 2 revealed that trait affectionate communication moderated these relationships, with those higher in trait affectionate communication who pretended to orgasm reporting the highest levels of trust, closeness, and commitment. The implications of these findings for theory and research on affectionate communication and sexual behavior are discussed.